2010
DOI: 10.1177/145749691009900110
|View full text |Cite
|
Sign up to set email alerts
|

Obesity May Impair the Early Outcome of Total Knee Arthroplasty a Prospective Study of 100 Patients

Abstract: We suggest that obesity may impair the early outcome of total knee arthroplasty and obese patients should be informed about the increased risk of complications related to TKA. Key words: Total knee arthroplasty; body mass index; obesity; complications; range of motion; mechanical axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 24 publications
6
44
1
1
Order By: Relevance
“…Our findings may be surprising considering that many orthopaedic surgeons hesitate to operate on obese patients who are prone to higher risks of component failures and worse outcomes [2,22]. Several recent studies [9,10,14,27] have examined the impact of obesity on function of TKA (Table 5). Although some authors reported no differences in the function between nonobese and obese patients during short-term and long-term followups [9,27], others have reported that severely obese patients had poorer function [10,18].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Our findings may be surprising considering that many orthopaedic surgeons hesitate to operate on obese patients who are prone to higher risks of component failures and worse outcomes [2,22]. Several recent studies [9,10,14,27] have examined the impact of obesity on function of TKA (Table 5). Although some authors reported no differences in the function between nonobese and obese patients during short-term and long-term followups [9,27], others have reported that severely obese patients had poorer function [10,18].…”
Section: Discussionmentioning
confidence: 87%
“…Fourth, we did not report complications and cannot comment on this issue. However, several studies [2,14,19,21] have reported obese patients had a higher number of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations